2021
DOI: 10.2147/jpr.s342928
|View full text |Cite
|
Sign up to set email alerts
|

Better Functional Outcome and Pain Relief in the Far-Lateral-Outside-in Percutaneous Endoscopic Transforaminal Discectomy

Abstract: Background Even though percutaneous endoscopic transforaminal discectomy (PETD) has been widely used for the surgical treatment of lumbar herniated disc, there are only a few studies directly comparing the clinical outcomes between microdiscectomy (MD) and PETD. Therefore, further studies are needed in order to compare the clinical outcomes between PETD and MD on a single level more thoroughly. Methods We proposed a far-lateral-outside-in technique for PETD to get an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…FETD, one of the most popular minimally invasive spinal surgeries, employs precise decompression with a narrow operative view and relies on fluoroscopic guidance. Although previous studies have demonstrated a high success rate for this technique [ [7] , [8] , [9] ], Choi et al reported that an incomplete removal of herniated discs as a complication of FETD, accounted for 64.9% of unsuccessful cases [ 20 ]. In a review article, Pan et al also reported that incomplete disc removal was one of the complications of FETD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FETD, one of the most popular minimally invasive spinal surgeries, employs precise decompression with a narrow operative view and relies on fluoroscopic guidance. Although previous studies have demonstrated a high success rate for this technique [ [7] , [8] , [9] ], Choi et al reported that an incomplete removal of herniated discs as a complication of FETD, accounted for 64.9% of unsuccessful cases [ 20 ]. In a review article, Pan et al also reported that incomplete disc removal was one of the complications of FETD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that both FETD [ [7] , [8] , [9] , [10] ] and UBEFLA [ [11] , [12] , [13] ] produce similar or even superior outcomes relative to MD. With advancements in surgical techniques and outcomes, FETD and UBEFLA have been widely applied for treating lumbar FS.…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, Wang et al reported better functional outcomes and pain relief with percutaneous endoscopic transforaminal discectomy compared with microdiscectomy, further supporting the efficacy of endoscopic approaches in spinal surgeries. 27…”
Section: Discussionmentioning
confidence: 99%